Analisis Kemampuan Berpikir Kritis Mahasiswa Pasca Pembelajaran Daring - Hasnawati Hasnawati; Arif Widodo (Departement of Mathematics Education, 2023)
Critical thinking skills are an important element that students must have in elementary science learning. Therefore, it is necessary to reveal students' critical thinking abilities in elementary school science learning. Moreover, looking at post-pandemic conditions or online learning in the last few semesters, this research aims to analyze the profile of critical thinking abilities of PGSD students after online learning. According to Peter A, Facione, critical thinking indicators used as a reference in this research include: interpretation, analysis, explanation, inference, evaluation and self-regulation. The research carried out is a type of quantitative research with a descriptive approach. The research subjects were 118 randomly selected students in the second semester of PGSD FKIP Unram who were programming elementary school science education courses. Students' critical thinking ability categories are categorized into 3, namely high, medium and low. The analysis results showed that 19 people or 16.10% of the sample measured had high critical thinking abilities, 82 people or 69.49% of people had moderate critical thinking abilities and the remaining 17 people or 14.41% were still in the low category. So it is necessary to improve the quality of lectures in order to improve students' critical thinking skills, especially prospective elementary school teachers